A review on microstrip patch antenna for wireless communication systems at 3.5 GHz - Rana, Md. Sohel; Chakrobortty, Paris; Pal, Sourav; Rahman, Md. Mahmudur; Sarker, Arpon; Saha, Pranto; Rahman, Sohanur (Bulletin of Electrical Engineering and Informatics, 2024)
This article presents a review of several microstrip patch antennas for 3.5 GHz wireless applications. Different substrate materials, FR-4 (loss), FR-4 Epoxy, Rogers RT/droid 5880, TLC-30, and Rogers RT/droid 5880 LZ, are used. In recent years, wireless antenna applications have increased, including biomedical appliances, internet of things (IoT) terminals, edge devices, radars, mobile phones, and many more. In this work, several articles were reviewed and investigated, and several microstrip patch antennas with a resonance frequency of 3.5 GHz were designed using different substrate materials and shapes. This article also discussed the geometric shapes of antennas, antenna properties, sizes of substrate materials, loss tangent, thickness, return loss, bandwidth, voltage standing wave ratio (VSWR), gain, efficiency, and directivity. Several software is used for design and simulation, including computer simulation technology (CST), high-frequency simulation frequency (HFSS), and advanced design system (ADS), FEKO, and MATLAB. The main goal of this paper is to talk about different wireless application papers that work in the S-band at a frequency of 3.5 GHz and have been published in various international journals and conferences.